Volunteering for a lifetime? Volunteers’ intention to stay in Portuguese hospitals - Ferreira, Marisa R. (2013)
Purpose – The current study aims to study Hospital volunteers’ intention to stay in an organization through understanding motivation, management factors and satisfaction. Design/methodology/approach – A total of 304 Hospital volunteers, mainly women, completed a questionnaire measuring motivations, management factors, satisfaction and intention to stay. In this study structural equation modelling was used. Findings – Results demonstrate that there is a positive relationship between (a) motivation and satisfaction, (b) management factors and satisfaction, (c) satisfaction and intention to stay and (d) motivation and management factors. These results present important outcomes that should be reflected in the way organizations operate. Research limitations/implications – This research was restricted to a health care context and to the opinion of only one stakeholder (volunteers). We assume volunteer intent to stay is a main predictor of retention. However, there are other variables not considered here that might influence intent to stay. Practical implications – This research indicates aspects which are most valued by volunteers and allows NPOs to design and establish appropriate and assertive management policies. Originality/value – The value of this paper is that it looks at understanding what factors influence volunteers’ intention to stay.